2020
DOI: 10.1002/prp2.561
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cytochrome P450s involved in oxidative metabolism of synthetic cannabinoid N‐(adamantan‐1‐yl)‐1‐(5‐fluoropentyl)‐1H‐indole‐3‐carboxamide (STS‐135)

Abstract: Synthetic cannabinoids (SCBs), designer drugs marketed as legal alternatives to marijuana, act as ligands to cannabinoid receptors; however, they have increased binding affinity and potency, resulting in toxicity symptoms such as cardiovascular incidents, seizures, and potentially death. N‐(adamantan‐1‐yl)‐1‐(5‐fluoropentyl)‐1H‐indole‐3‐carboxamide (STS‐135) is a third generation SCB. When incubated with hepatocytes, it undergoes oxidation, hydrolysis, and glucuronidation, resulting in 29 metabolites, with mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Whilst the number of substances detected by toxicology in SCRA-related decedents dramatically increased from 2012 to 2019, evidence for SCRA drug-drug interactions remains scarce. Studies indicate that some SCRA types interact with cytochrome P450 pathways, which may negatively impact the pharmacodynamics of other co-administered substances leading to adverse events (61)(62)(63)(64)(65)(66)(67)(68)(69)(70). However, these studies used older SCRA types, which differ substantially in terms of molecular structure to those which are currently prevalently used (42).…”
Section: Knowledge Of Scra-disease/drug Interactions Is Scarcementioning
confidence: 99%
“…Whilst the number of substances detected by toxicology in SCRA-related decedents dramatically increased from 2012 to 2019, evidence for SCRA drug-drug interactions remains scarce. Studies indicate that some SCRA types interact with cytochrome P450 pathways, which may negatively impact the pharmacodynamics of other co-administered substances leading to adverse events (61)(62)(63)(64)(65)(66)(67)(68)(69)(70). However, these studies used older SCRA types, which differ substantially in terms of molecular structure to those which are currently prevalently used (42).…”
Section: Knowledge Of Scra-disease/drug Interactions Is Scarcementioning
confidence: 99%
“…The substrate (final concentration 1-400 µM) was added to each tube (50 µL) along with protein, water, and buffer (final concentration 0.1 M KPO 4 , pH 7.4); the reactions were started with the addition of an NADPH-regenerating system (1 mM NADP + , 3 mM glucose 6-phosphate, 3 mM MgCl 2 ; 1 U/mL glucose 6-phosphate dehydrogenase) to ensure the saturation of NADPH, thus enabling cytochrome P450mediated reactions. As described previously in Jones et al (2020) [29], we used up to 50 µg of enzyme sources for each incubation tube. We confirmed that we observed the enzyme activity in a protein amount-dependent manner.…”
Section: Metabolism Of Jwh-019 In Hlms and Recombinant P450smentioning
confidence: 99%
“…134, Exclusive use of human liver microsomes has been used to study the metabolism of, MMB022, 3,5-AB-CHMFUPPYCA, ADB-FUBINACA, 5F-ADB, CUMYL-PINACA, CUMYL-4CN-B7AICA, CUMYL-4CN-BINACA, 5F-CUMYL-PINACA, AKB-48, STS-135, MAM-2201 and XLR-11 among others. 136,[164][165][166][167][168][169][170][171] The following synthetic cannabinoids have been studied using only hepatocytes, BB-22, 5C-AKB48, EG-018, PB-22, 5F-PB-22 SDB-006, AKB-48 and XLR-11 among others. [172][173][174][175][176][177][178] Several metabolism studies of synthetic cannabinoids in urine have been carried out, including of ADB-FUBINACA, AM-694, AM-2201, JWH-007, JWH-019, JWH-203, JWH-307, MAM-2201, UR-144, XLR-11, APINAC, BB-22, EG-018, EG-2201, MDMB-CHMCZCA, MDMB-FUBINACA and 5Cl-THJ-018.…”
Section: Synthetic Cannabinoidsmentioning
confidence: 99%